A 2-D distributed power combining by metamaterial-based zero phase shifter for 60-GHz power amplifier in 65-nm CMOS - Fei, Wei (2013)
Based on a newly introduced zero phase shifter (ZPS), a 2-D distributed power-combining network is developed in this paper to provide simultaneous distributed amplification and power combining. One type of metamaterial, called the composite right/left-handed transmission line, is deployed to design ZPS with detailed considerations to achieve low loss and wideband performance. The proposed 2-D distributed power combining is implemented for one 60-GHz power amplifier (PA) design by a UMC standard 65-nm CMOS process. Measured results show that the fabricated PA has 0.39- mm2 area, 8.3-dB gain, 7.1% power-added efficiency, and 9.7-dBm P1 dB with 16-GHz bandwidth (44-60 GHz).